2008
DOI: 10.1002/ijc.24082
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell‐mediated lysis of freshly isolated human tumor cells

Abstract: Studies on interactions between natural killer (NK) cells and freshly isolated human tumor cells are still relatively scarce. With respect to the understanding of NK cell interactions with human tumors in vivo, and attempts to better predict the outcome of NK cell-mediated adoptive immunotherapy, such studies merit further attention. They may provide information that is not readily evident through studies of human tumor cell lines established through long-term culturing in vitro. The latter undergo several cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 69 publications
(115 reference statements)
0
25
0
Order By: Relevance
“…41,42 NK-cell recognition of myeloma seems to depend primarily on DNAM-1, whereas recognition of AML primarily relies on NKG2D. 21 Similarly, a role for NKG2D has been suggested in NK cellmediated killing of the MDS clone. 25,43 However, those experiments were based on one MDS cell line (MDS1) and not on primary blasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41,42 NK-cell recognition of myeloma seems to depend primarily on DNAM-1, whereas recognition of AML primarily relies on NKG2D. 21 Similarly, a role for NKG2D has been suggested in NK cellmediated killing of the MDS clone. 25,43 However, those experiments were based on one MDS cell line (MDS1) and not on primary blasts.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, by studying the recognition of freshly isolated blasts, we show a dominant role for DNAM-1 in the recognition of MDS. Given the crucial role for DNAM-1 and NKG2D in the recognition of several human tumors 21 and in immune surveillance against tumors in mice, 19,20 it is tempting to speculate that reduced expression of these receptors may have consequences in the disease progression and in the malignant transformation of MDS to AML. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies provide the first direct evidence for a central role for DNAM-1 in tumor immune surveillance. DNAM-1 is important for NK cell-mediated recognition of several human tumors, including neuroblastoma, myeloma, and Ewing sarcoma (16,17,29,35). We have previously shown that the DNAM-1/CD155 interaction is crucial for the recognition of freshly isolated ovarian carcinoma by allogeneic NK cells (15).…”
Section: Tumor-associated Nk Cells Fail To Target Autologous Tumor Cementioning
confidence: 99%
“…From the perspective of ovarian cancer, the NKG2D and DNAM-1 receptor systems are of importance because ovarian tumors express ligands for these two receptors (23,(71)(72)(73)(74)(75). It has been proposed that naïve or activated autologous NK cells can mediate cytolysis of ovarian tumors because of the expression of NKG2D and DNAM-1 ligands by ovarian tumors (76). However, it should be noted that the killing of ovarian tumor cells by NK cells is significantly lower than the killing observed with NK cell susceptible targets ( Figure 3).…”
Section: Anti-tumor Immune Responsementioning
confidence: 99%